Analysis of Customer Preference Factors for Qardh and Murabahah Products at Bank BRI Syariah of Bungo Regency - Rahman Arifin; Busriadi Busriadi (AL-FALAH : Journal of Islamic Economics, 2020)
Purpose: This research was conducted at BRI Syariah KCP Muara Bungo, this was done because the researchers wanted to find out the influence of customer preferences using qardh and muarabah products with sharia system variables, products, services, places / locations and promotions to customer preferences at BRI Syariah KCP Muara Bungo.Design/Method/Approach:. This study uses a descriptive analysis approach and quantitative methods with the aim of examining the influence between variables studied through hypothesis testing. This study uses the Slovin formula to obtain sample sizes, for data analysis methods using multiple linear regression equation models. The assistance used is the SPSS statistical data processing program version 21.00. windows.Findings: The results showed that overall (simultaneous) there was a significant influence between variables consisting of sharia system variables, products, services, places / locations and promotions to customer preferences in BRI Syariah Muara Bungo KCP. While the variable that has the most influence is promotion (X5), because it has the highest regression coefficient.Originality/Values: Novelty of the study identified from issue studied constitently, and also place of where the study researched.